Record Breakers - Winchester, Jim. (Milwaukee, Wi Gareth Stevens Publishing, 2007)
Highlights the aircraft used to make the very first, the fastest, the farthest, and the highest flights. Other amazing aircraft allowed such feats as breaking the sound barrier, flying nonstop around the world without refueling, and crossing the English Channel on pedal power alone. Every chapter focuses on the features that make each craft special.
5 - 9
Keywords: Aeronautics - Records; Aircraft; Aircraft of the World